Transformational Leadership and Educators’ Creative Performance: The Roles of Self-Efficacy and Intrinsic Motivation - Tanoto, Sherly Rosalina; Dewanti , Antonieta Widya (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
In digitally mediated and technology-intensive educational environments, educators are increasingly required to demonstrate creative performance to sustain learning quality and organizational competitiveness. Previous studies on the connection between transformational leadership and creative performance show inconsistent results. This study investigates the effect of transformational leadership, creative self-efficacy, and intrinsic motivation on creative performance within the education sector in Malang. This study uses a quantitative approach by collecting data from 202 educators. Partial Least Squares was implemented to examine the research model. The results showed that transformational leadership affected creative performance, creative self-efficacy, and intrinsic motivation. Creative self-efficacy significantly enhances creative performance and partially mediates the relationship between transformational leadership and creative performance, whereas intrinsic motivation does not demonstrate a significant direct or mediating effect. The model explains 62.4% of the variance in creative performance. These findings provide suggestions and practical implications for educators and leaders of educational institutions. It also offers theoretical insights that the association between transformational leadership, intrinsic motivation, and creative performance is complex.